Spirinia elongata, sp. nov. (Nematoda, Desmodoridae) from Pina Basin, Pernambuco, Brazil - de Castro, Francisco J.v.; Bezerra, Tânia N.c.; Da Silva, Maria C.; Fonsêca-Genevois, Verônica (Zootaxa, 2006)
A new species Spirinia elongata sp. nov., is described from the Pina Basin a hypereutrophic estuary on the coast of Pernambuco state (Brazil). The new species belongs to the Desmodoridae and is distinguished from all known valid species of the genus by the presence of two dorsal teeth and one ventral tooth.